2016
DOI: 10.1155/2016/9345495
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin Cleavage of Osteopontin Modulates Its Activities in Human CellsIn Vitroand Mouse Experimental Autoimmune EncephalomyelitisIn Vivo

Abstract: Osteopontin is a proinflammatory cytokine and plays a pathogenetic role in multiple sclerosis and its animal model, experimental autoimmune encephalomyelitis (EAE), by recruiting autoreactive T cells into the central nervous system. Osteopontin functions are modulated by thrombin cleavage generating N- and C-terminal fragment, whose individual roles are only partly known. Published data are difficult to compare since they have been obtained with heterogeneous approaches. Interestingly, thrombin cleavage of ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 64 publications
(64 reference statements)
1
50
0
Order By: Relevance
“…Since the thrombin cleavage site in OPN is in the middle of these putative sequences, the ability to bind ICOSL displayed by recombinant forms of the N-term (aa 17–167) and C-term (aa 168–314) portions of OPN was tested; these correspond to the two fragments generated by the physiologic thrombin cleavage of the whole OPN (Fig. 6a ) 12 . ELISA assay showed that both the OPN portions bind to ICOSL, but to a lesser extent than the full-length protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the thrombin cleavage site in OPN is in the middle of these putative sequences, the ability to bind ICOSL displayed by recombinant forms of the N-term (aa 17–167) and C-term (aa 168–314) portions of OPN was tested; these correspond to the two fragments generated by the physiologic thrombin cleavage of the whole OPN (Fig. 6a ) 12 . ELISA assay showed that both the OPN portions bind to ICOSL, but to a lesser extent than the full-length protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Osteopontin (OPN) is a phosphoprotein, secreted by several cell types, such as macrophages, DC and Th cells; it can function both as a matricellular protein and a cytokine mediating several biological functions. These include migration, adhesion, activation of inflammatory cells, and modulation of T cell activation supporting differentiation of proinflammatory type 1 (Th1) and type 17 (Th17) Th cells 12 . It is highly expressed in several types of tumors, being secreted by both tumor and microenvironment cells, and is implicated in promoting tumor invasion and metastatic dissemination 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Gong et al reported that intranasal administration of rOPN dose-dependently increased OPN expression in brain tissue after hyperglycemic intracerebralhemorrhage. 16 In the current study, considering the reported importance of thrombin and metalloproteinases-cleaved OPN after SAH, 31,32 we used Western blot analysis to examine the amount of full-length OPN and cleaved OPN variants in the left hemisphere (the perforation side) after SAH and rOPN intranasal administration. Our results showed a significant increase in the amount of all variants of OPN, which includes both full-length and cleavage products at 24 hours after SAH.…”
Section: Ropn Administration Influenced the Interaction And Balancementioning
confidence: 99%
“…In several cell types, including vascular endothelial cells and tumor cells, OPN-N induces migration whereas OPN-C induces adhesion. By contrast, both fragments similarly induce IFN- γ secretion in T cells and tubulogenesis in vascular endothelial cells and inhibit activation-induced cell death in lymphocytes [42]. …”
Section: Introductionmentioning
confidence: 99%